2015
DOI: 10.1111/adb.12320
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and prefrontal stress system markers and risk of relapse in alcoholism

Abstract: Previous research has shown that hyperactivation in ventral medial prefrontal cortex (VmPFC) and rostral anterior cingulate cortex (rACC) and high cortisol to corticotrophin ratio (cort:ACTH ratio) during neutral-relaxed states predict relapse in alcohol dependent (AD) patients. Other studies have shown that VmPFC/rACC deactivation and blunted cortisol release to stress and alcohol cues are predictive of time to relapse and relapse severity. However, no previous study has assessed the relationship between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
(61 reference statements)
1
29
0
Order By: Relevance
“…In a series of studies in our laboratory, participants were exposed to stress, alcohol cue, and neutral imagery paradigms both in the laboratory and during fMRI scans. Findings indicated that craving, adrenal sensitivity, and VmPFC hypoactivity following exposure to stress-related and alcohol cue-related imagery predicted shortened time to relapse, such that disrupted neutral state PFC function appears to mediate the relationship between adrenal sensitivity and future relapse risk (Blaine et al, 2015). Importantly, the study findings indicate that heightened peripheral tonic arousal may be associated with diminished prefrontal executive control over striatal and limbic circuits during stress in those with severe AUDs in early abstinence.…”
Section: Hpa Axis and Prefrontal Dysregulation Increase Cue Reactimentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies in our laboratory, participants were exposed to stress, alcohol cue, and neutral imagery paradigms both in the laboratory and during fMRI scans. Findings indicated that craving, adrenal sensitivity, and VmPFC hypoactivity following exposure to stress-related and alcohol cue-related imagery predicted shortened time to relapse, such that disrupted neutral state PFC function appears to mediate the relationship between adrenal sensitivity and future relapse risk (Blaine et al, 2015). Importantly, the study findings indicate that heightened peripheral tonic arousal may be associated with diminished prefrontal executive control over striatal and limbic circuits during stress in those with severe AUDs in early abstinence.…”
Section: Hpa Axis and Prefrontal Dysregulation Increase Cue Reactimentioning
confidence: 99%
“…Both responses predicted future return to alcohol intake (Reproduced with permission from Blaine et al, Addiction Biology, 2015). …”
Section: Figurementioning
confidence: 99%
“…There is now strong evidence that the mammalian response to stress is an orchestration of endocrine, neural and behavioral processes that, in the face of chronic alcohol, can become maladaptive and propagate further escalations in alcohol intake (Becker, 2012; Blaine et al, 2015; Sinha et al, 2011). This underscores the phenomenon that the relationship between stress and alcohol is bidirectional.…”
Section: I: Introductionmentioning
confidence: 99%
“…This sensitization might foster alcohol misuse and stress-induced relapse, because of the anxiolytic and stress-dampening effects of alcohol at inhibitory gamma-aminobutyric acid (GABA) receptors and the reduction of glutamatergic signaling by actions at N-methyl-Dasparate (NMDA) receptors (Anthenelli 2012). However, alcohol consumption has also been associated with enhanced NA levels in several studies (Anthenelli 2012;Blaine et al 2016;Fitzgerald 2013). In accordance with these findings, an increased sympathetic tone as indicated by elevated blood pressure and heart rate parameters has been reported after alcohol intake (Ireland et al 1984;Kelbaek et al 1988;Spaak et al 2010).…”
Section: Introductionmentioning
confidence: 69%
“…Autonomic dysregulations with an increased sympathetic and a decreased vagal tone have been observed during chronic alcohol misuse (Ingjaldsson et al 2003;Quintana et al 2013). The hyperaroused state persists or rather increases during the first days after detoxification (Blaine et al 2015;Kahkohen 2004;Karpyak et al 2014) but decreases continuously when abstinence is maintained (Adinoff et al 2005;Adinoff et al 1990;Kahkohen 2004;Patkar et al 2003). Despite this reduction of physical arousal, a persistent dysregulation with elevated basal heart rate and enhanced basal HPA activity in AD patients could be observed during the first weeks of abstinence (Ehrenreich et al 1997;Sinha et al 2009).…”
Section: Introductionmentioning
confidence: 99%